A Pragmatic Approach to Designing Changes Using Convergent Interviews: Occupational Violence Against Paramedics as an Illustration. Issue 2 (5th June 2018) - Thynne, Lara; Rodwell, John
Abstract: Developing a change program to address complex problems can appear overwhelming. This study presents how an inductive diagnostic technique known as convergent interviewing can provide a summary of the critical issues that could be addressed by a change program. A systems perspective is used to show how the issues raised by the diagnostic process can be targeted in order to have the most effect and be pragmatically implementable. The use of the tool is illustrated by analysing an employee problem that needs to be addressed in public services, the high rates of occupational violence against paramedics. The resulting inductive systems model can be used for diagnosis or for informing a variety of change interventions. Convergent interviews are relatively easy to use, powerful, and applicable to many situations. This tool is particularly useful for developing innovations regarding a specific problem, changes that could be a source of substantial public value. Abstract : Convergent interviews can design organizational changes, particularly changes oriented toward addressing problems representing substantial public value. The problem of occupational violence against paramedics is used to illustrate the process and how the results can be leveraged from a systems perspective.